1981
DOI: 10.1002/bjs.1800680606
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of heterotopic pancreas in the gastrointestinal tract

Abstract: A series of 34 histologically verified cases of pancreatic heterotopia in the records of the Department of Pathology at the University of Edinburgh between 1959 and 1979 has been analysed in order to determine the clinical significance of this unusual condition. In 13 patients (38 per cent) the heterotopic pancreatic tissue was symptomatic (i.e. the symptoms regressed completely on its removal). A correlation has been established between the presence of symptoms, the size of the lesion and the extent of mucosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
135
0
7

Year Published

1983
1983
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(148 citation statements)
references
References 12 publications
6
135
0
7
Order By: Relevance
“…Adenocarcinomas arising from ectopic pancreas seem to have a somewhat better prognosis than those arising from the pancreas itself, probably due to earlier presentation [10] . Symptoms depending upon the anatomical location, such as gastric outlet obstruction in a pre-pyloric rest or obstructive jaundice in a bile duct focus, may originate from the mass effect of the tumour [12] and are also related to the size of the lesion. Lesions greater than 1.5 cm in diameter are more likely to cause symptoms [12] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adenocarcinomas arising from ectopic pancreas seem to have a somewhat better prognosis than those arising from the pancreas itself, probably due to earlier presentation [10] . Symptoms depending upon the anatomical location, such as gastric outlet obstruction in a pre-pyloric rest or obstructive jaundice in a bile duct focus, may originate from the mass effect of the tumour [12] and are also related to the size of the lesion. Lesions greater than 1.5 cm in diameter are more likely to cause symptoms [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms depending upon the anatomical location, such as gastric outlet obstruction in a pre-pyloric rest or obstructive jaundice in a bile duct focus, may originate from the mass effect of the tumour [12] and are also related to the size of the lesion. Lesions greater than 1.5 cm in diameter are more likely to cause symptoms [12] . Pain is one of the most common symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heartburn and dyspepsia are also frequent for gastric HP, but often there are symptoms due to mechanical obstruction [1] . In the series of 34 patients with pancreatic heterotopia of Armstrong et al, 8 lesions were located in the stomach and 6 of those had produced symptoms [8] .…”
Section: Discussionmentioning
confidence: 99%
“…Armstrong et al found that symptoms are related to the size of HP lesion. They postulated that size greater than 1.5 cm is more likely to be of clinical significance [8] . Other less common symptoms were bleeding mimicking jejunal tumor [9] , pancreatitis, and malignant transformation [10][11][12] .…”
Section: Discussionmentioning
confidence: 99%